Association between testosterone levels and risk of future rheumatoid arthritis in men: a population-based case–control study. Issue 3 (3rd April 2013) - Pikwer, Mitra; Giwercman, Aleksander; Bergström, Ulf; Nilsson, Jan-Åke; Jacobsson, Lennart T H; Turesson, Carl
Abstract : Objectives: Rheumatoid arthritis (RA) is less common among men than women, and sex hormones have been suggested to play a part in the pathogenesis. Lower levels of testosterone have been demonstrated in men with RA, but it is not known if these changes precede the disease. Methods: In a nested case–control study, using information and blood samples from a population-based health survey, we identified incident cases of RA by linking the cohort to local and national RA registers. Two controls for each validated case, matched for age, sex and year of screening, were selected from the health survey. Using stored blood samples, collected between 08:00 and 10:00 am after an overnight fast, we analysed levels of testosterone and other reproductive hormones. Results: Serum was available from 104 cases (median time from screening to RA diagnosis 12.7 years (range 1–28); 73% rheumatoid factor (RF) positive at diagnosis or later) and 174 matched controls. In conditional logistic regression models, adjusted for smoking and body mass index, lower levels of testosterone were associated with subsequent development of RF-negative RA (OR 0.31 per SD, 95% CI 0.12 to 0.85), with a weaker association with RF-positive RA (OR 0.87 per SD; 95% CI 0.53 to 1.43). Levels of follicle-stimulating hormone were significantly increased in pre-RF-negative RA (p=0.02), but decreased in pre-RF-positive RA (p=0.02). Conclusions: Lower levels of testosterone were predictive of RF-negative RA, suggesting that hormonal changes precede the onset of RA and affect the disease phenotype.